Roma in Bosnia-Herzegovina: A Gendered Gaze at the Politics of Roma, (I)NGOs, and the State: Ромите во Босна и Херцеговина: Родов поглед на ромската политика, (М)НВО и државата - Erickson, Jennifer; Jakimovska, Jana (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Jennifer Erickson | Џенифер Ериксон Title (English): Roma in Bosnia-Herzegovina: A Gendered Gaze at the Politics of Roma, (I)NGOs, and the State Title (Macedonian): Ромите во Босна и Херцеговина: Родов поглед на ромската политика, (М)НВО и државата Translated by (English to Macedonian): Jana Jakimovska | Јана Јакимовска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 87-128 Page Count: 41 Citation (English): Jennifer Erickson, “Roma in Bosnia-Herzegovina: A Gendered Gaze at the Politics of Roma, (I)NGOs, and the State,” Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 87-128. Citation (Macedonian): Џенифер Ериксон, „Ромите во Босна и Херцеговина: Родов поглед на ромската политика, (М)НВО и државата“, превод од англиски Јана Јакимовска, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 87-128.